Gambaran Klinikopatologi Parapsoriasis - Puspitasari, Galuh; Yuniaswan, Anggun; Retnani, Diah (Jurnal Klinik dan Riset Kesehatan, 2021)
Parapsoriasis is a dermatoses which reflect clinical overlap includes chronicity, recalcitrans, idiopathic causes against the therapy, and the lesions often nonpruritic, which resembles to psoriasis. There are two common forms of parapsoriasis i.e. small plaque parapsoriasis (SPP) and a large plaque parapsoriasis (LPP). Many skin diseases have symptoms that resemble parapsoriasis, so the diagnosis is difficult to establish. Therefore histopathological and immunohistochemical examination needs to be done. Parapsoriasis is characterized by superficial cutaneous lymphoid infiltrates consisting of T cells in histopathological examination both on LPP and SPP. But, LPP infiltrates often contain lymphocytes with cerebriform nuclei (Lutzner cells) that are similar to Sezary cells in Mycosis fungoides (MF). Immunohistochemical examination of CD3 can show that T cells are normal or atypical if they lead to a malignancy. Therefore, evaluation of T cell density on histopathological features and CD3 immunohistochemical examination can help establish the diagnosis of parapsoriasis, as well as to recognize signs of malignancy leading to MF.